2007
DOI: 10.1211/jpp.59.12.0015
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of 4-methylcoumarins

Abstract: Polyphenolic coumarins are known to act as antioxidants in biological systems, but it is difficult to distinguish their antioxidant activity from the many other effects they produce in cells. We have determined the radical scavenging capacity of 22 structurally related natural and synthetic 4-methylcoumarins, by measuring their reaction with radicals, galvinoxyl and 2,2-diphenyl-1-picrylhydrazyl, using electron paramagnetic resonance spectroscopy. Efficient antioxidant activity of 4-methylcoumarins in cells wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 25 publications
5
47
0
Order By: Relevance
“…They are present at high levels in cinnamon and many fruits and vegetables (Krieger et al, 2013;Ribeiro da Silva et al, 2014). Different derivatives of these compounds possess a wide range of biological activities (Venugopala et al, 2013) such as antioxidant (Morabito et al, 2010;Natella et al, 2010;Pedersen et al, 2007), anti-inflammatory (Togna et al, 2014), antimicrobial (Gupta et al, 2012), and in vitro (Macakova et al, 2012) and in vivo platelet anti-aggregation effects .…”
Section: Introductionmentioning
confidence: 99%
“…They are present at high levels in cinnamon and many fruits and vegetables (Krieger et al, 2013;Ribeiro da Silva et al, 2014). Different derivatives of these compounds possess a wide range of biological activities (Venugopala et al, 2013) such as antioxidant (Morabito et al, 2010;Natella et al, 2010;Pedersen et al, 2007), anti-inflammatory (Togna et al, 2014), antimicrobial (Gupta et al, 2012), and in vitro (Macakova et al, 2012) and in vivo platelet anti-aggregation effects .…”
Section: Introductionmentioning
confidence: 99%
“…23,26) 4-Methylcoumarin derivatives bearing 7,8-dihydroxy and 7,8-diacetoxy moieties have been reported to be potent antioxidant compounds. [12][13][14] Most of these reports have suggested that 7,8-dihydroxy confers higher activity compared to 7,8-diacetoxy, 13,14) probably due the important contribution of catechol moiety to the antioxidant activity. However, in some papers this difference seems to be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,15,16) 4-Methylcoumarins bearing 7,8-ortho-dihydroxy or 7,8-orthodiacetoxy moieties have been found to be better radical scavengers and antioxidants. 12,17) On the other hand, the insertion of ethoxycarbonylmethyl moiety at C3 position does not lower the activity of these compounds and may increase the lipophilicity. 14) Increased lipophilicity is a very important physicochemical property that enables the compound to cross the cell membranes and reach its intracellular targets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Coumarins and their derivatives have attracted intense interest in recent years because of their diverse pharmacological properties: many coumarin derivatives have the special ability to scavenge reactive ROS and to influence processes involving free radical injury. In particular both esculetin and a novel synthetic 4-methylcoumarin, 4-methylesculetin (ESC), possess two hydroxyl moieties on their benzene rings, and these were the two most effective radical scavengers among the coumarins selected for a structure-activity relationship study in cell culture [41] . Beyond its antioxidant activity, ESC is able to lower HMGR activity reducing PP2A protein levels leading to HMGR hyperphosphorylation.…”
Section: Coumarinsmentioning
confidence: 99%